Interação genótipo ambiente sobre o desempenho ponderal de animais da raça Nelore na região Centro-Oeste - Santos, Cleide Lis Ribeiro dos (2016)
The aim was to evaluate the genotype x environment interaction on the body weights at 120 (P120) 210 (P210) 365 (P365) and 450 (P450) days of age from 30,481 Nelore cattle breed, offsprings of 211 sires mated with 19,229 dams from 12 herds in the states of Mato Grosso state (MT), Mato Grosso do Sul (MS) and Goiás (GO). To estimate variance components and subsequent prediction of breeding value of sires for body weights was adopted the model for unitrait (general analysis) and for multtrait analysis (using the same trait expressed in different states as different traits) including the fixed effects of related group of contemporary, linear and quadratic effect of age of calving, in addition to random effects additive genetic of the animals, maternal genetic (for P120 and P210), maternal permanent environmental effect and temporary environment. The prediction the breeding value of sires were udes to obtained Spearman correlation for sires with producing as well as the 100, 75, 50 and 25% of the best sires ranked in the general analysis. Genetic trend for all the weights in the overall analysis and in each state by linear regression of breeding values of the sires, depending on the year of birth of their offspring were also obtained. The heritability estimates for P120, P210, P365 and P450 between the state ranged from 0.09 to 0.14; 0.11 to 0.17; 0.16 to 0.27 and 0.17 to 0.35 respectively. All estimates of additive genetic correlation between the same trait for the different states had values below 0.80. The increase of the selective intensity ampified the effect of genotype x environment interaction. The best sires classified in a state, for a given trait based on genetic merit, were not necessarily the best classified in the other states. Estimates of genetic trends for all body weights increased over the years in the three states.